2001
DOI: 10.1038/84818
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models for Friedreich ataxia exhibit cardiomyopathy, sensory nerve defect and Fe-S enzyme deficiency followed by intramitochondrial iron deposits

Abstract: Friedreich ataxia (FRDA), the most common autosomal recessive ataxia, is characterized by degeneration of the large sensory neurons and spinocerebellar tracts, cardiomyopathy and increased incidence in diabetes. FRDA is caused by severely reduced levels of frataxin, a mitochondrial protein of unknown function. Yeast knockout models as well as histological and biochemical data from heart biopsies or autopsies of FRDA patients have shown that frataxin defects cause a specific iron-sulfur protein deficiency and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

54
685
2
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 682 publications
(746 citation statements)
references
References 22 publications
54
685
2
5
Order By: Relevance
“…To this end, we examined the Fe metabolism of MCK mutants and the potential of Fe chelation to prevent cardiomyopathy. This model was chosen as it closely reflects the alterations in the heart of FA patients, including MIT Fe loading (5). The Fe accumulation is observed only after 7 weeks of age, with no detectable deposits being found earlier (5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, we examined the Fe metabolism of MCK mutants and the potential of Fe chelation to prevent cardiomyopathy. This model was chosen as it closely reflects the alterations in the heart of FA patients, including MIT Fe loading (5). The Fe accumulation is observed only after 7 weeks of age, with no detectable deposits being found earlier (5).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies infer a role for Fxn in MIT iron (Fe) metabolism, particularly iron-sulfur cluster (ISC) biosynthesis (2,3). Deletion of the yeast Fxn homolog 1 gene or loss of Fxn in FA patients or Fxn knockout (mutant) mice promotes MIT Fe accumulation, hypersensitivity to oxidants, and the loss of MIT DNA and ISC-containing enzymes (2)(3)(4)(5). Increased cardiac Fe deposition and perturbations in heme biosynthesis and ATP production suggest that FA pathogenesis is linked to MIT Fe overload (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In patients and various models of Friedreich's ataxia, Fe-S cluster biogenesis and iron metabolism are impaired 2,3 . Initial studies on eukaryotic and prokaryotic FXNs suggested roles in iron storage 4 , delivery 5 and detoxification 6 , but the physiological relevance of these functions has been questioned [7][8][9][10] .…”
mentioning
confidence: 99%
“…Plusieurs souris invalidées pour le gène de la frataxine ont été produites par une technique de ciblage génique conditionnel. Elles développent les principales lésions observées au cours de la maladie humaine : atteinte du cervelet et du ganglion spinal [45], cardiomyopathie [46] et diabète [47]. Elles ont permis de tester de nouvelles molé-cules thérapeutiques.…”
Section: Modèles Transgéniques De Neurodégénérescence Autosomique Récunclassified